Model Relasi Islam Dan Negara Di Indonesia - Dadang Darmawan (UIN Sunan Gunung Djati Bandung, 2017)
This article discusses how the relationship between Indonesia and the Islamic community in Indonesia is represented by Islamic affiliated organizations in early independence until the reformation period in 1998. See the growing phenomenon of many religious organizations that emerge from fundamental, radical, secular to syncretism. Upheavals between the government and religious organizations to bring the phenomenon of Islamic archipelago. one theme that is being initiated between the government and the people of Islam Indonesia, which is expected to become an Islamic model that represents the nation of Indonesia in the eyes of the world.